IMPROVING THE QUALITY OF HUMAN RESOURCES IN MADRASAH - Yudik Al Farisi (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2021)
This study aims to understand how to create superior quality human resources in Madrasah Aliyah Nurul Jadid, Paiton, Probolinggo, East Java. This research is a case study qualitative research, in which researchers seek to understand the phenomena in improving the quality of superior human resources in madrasas. The results of this study indicate that the efforts made by madrasas in creating excellent quality human resources are carried out through, first, in-service training, namely education and training efforts to improve the competence and skills of teachers and employees. Second, the creation of an organizational culture that can encourage success. Third, making clear standard operating procedures to ensure that all decisions made are carried out correctly. Fourth, supervision and assessment as a medium that knows and measures the performance of existing resources.